Hannibal Lecter: the glamor of a psychopath through the lens of cinema (Research, Society and Development, 2022)
This article presents an analysis of the Antisocial personality disorder existing in the character Hannibal Lecter, from the television series Hannibal, released by NBC. The work presents a critical analysis of the disorder and how it is distorted by the film industry that romanticizes the actions and positions of the character Hannibal. This article aimed to present a critical analysis of the cinematographic novelization built for the psychopath Hannibal Lecter, in the series Hannibal. This research was a case analysis work, bibliographic procedure and qualitative approach. A television series was used as a case to be studied. The results show that the romanticization and glamorization of the acts of the character with antisocial personality disorder led the film industry to make several adaptations of the disorder and the character to express the typical symptoms of the pathology. It was also found that this distortion of the character's pathology aims to meet a commercial demand for mass entertainment, leading the viewer to "glamorize" the behaviors of a psychopath. In view of this, a critique of the fanciful demonstration of the mental disorders pointed out within the series in question was carried out, informing what is fiction and what is reality from analyzes and studies within psychology.